Effectiveness of adalimumab in treating patients with ankylosing spondylitis associated with enthesitis and peripheral arthritis - Rudwaleit, Martin (BioMed Central, 2010)
INTRODUCTION: The purpose of this study was to investigate the effectiveness of adalimumab in enthesitis and peripheral arthritis in patients with ankylosing spondylitis (AS). METHODS: Adults with active AS (Bath ankylosing spondylitis disease activity index [BASDAI] ≥ 4) received adalimumab 40 mg every other week with standard antirheumatic therapies in a 12-week, open-label study. Effectiveness in enthesitis was assessed using the Maastricht ankylosing spondylitis enthesitis score (MASES, 0-13) and by examining the plantar fascia in patients with enthesitis (≥ 1 inflamed enthesis) at baseline; effectiveness in peripheral arthritis was evaluated using tender and swollen joint counts (TJC, 0-46; SJC, 0-44) in patients with peripheral arthritis (≥ 1 swollen joint) at baseline. Overall effectiveness measures included Assessment of SpondyloArthritis International Society 20% response (ASAS20). RESULTS: Of 1,250 patients enrolled, 686 had enthesitis and 281 had peripheral arthritis. In 667 patients with MASES ≥ 1 at baseline, the median MASES was reduced from 5 at baseline to 1 at week 12. At week 12, inflammation of the plantar fascia ceased in 122 of 173 patients with inflammation at baseline. The median TJC in 281 patients with SJC ≥ 1 at baseline was reduced from 5 at baseline to 1 at week 12; the median SJC improved from 2 to 0. ASAS20 responses were achieved by 70.5% of 457 patients with no enthesitis and no arthritis; 71.0% of 512 patients with only enthesitis; 68.0% of 107 patients with only arthritis; and 66.7% of 174 patients with both. CONCLUSIONS: Treatment with adalimumab improved enthesitis and peripheral arthritis in patients with active AS. TRIAL REGISTRATION: ClinicalTrials.gov NCT00478660.